2022
DOI: 10.1186/s43141-022-00335-2
|View full text |Cite
|
Sign up to set email alerts
|

A local Talaromyces atroroseus TRP-NRC isolate: isolation, genetic improvement, and biotechnological approach combined with LC/HRESI-MS characterization, skin safety, and wool fabric dyeing ability of the produced red pigment mixture

Abstract: Background During the last decade, enormous research efforts have been directed at identifying potent microorganisms as sustainable green cell factories for eco-friendly pigments. Talaromyces atroroseus has recently been shown to excrete large amounts of azaphilone mycotoxin-free red pigment mixture comprising some known coloring components together with many uncharacterized metabolites. In this study, a new Talaromyces atroroseus isolate was identified via sequencing of the fragment of the nuc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 65 publications
0
0
0
Order By: Relevance
“…In addition, starch was the best for red pigment production by Paecilomyces sinclairii [36,37]. Mannitol was used as the best carbon source for production of red microbial pigments [38] Moreover, Sankhyayan et al [39] found that lactose and fructose strongly decreased pigment production.…”
Section: Selection Of Proper Carbon Sourcementioning
confidence: 99%
“…In addition, starch was the best for red pigment production by Paecilomyces sinclairii [36,37]. Mannitol was used as the best carbon source for production of red microbial pigments [38] Moreover, Sankhyayan et al [39] found that lactose and fructose strongly decreased pigment production.…”
Section: Selection Of Proper Carbon Sourcementioning
confidence: 99%
“…The source of natural pigments from microorganisms such as bacteria, algae and filamentous fungi are good alternatives because manipulating them is more controllable and they are suitable for large-scale production. Of the pigment-producing microorganisms, fungi are considered to be the best source due to their ability to synthesise more soluble and stable pigments [1].…”
Section: Introductionmentioning
confidence: 99%
“…1 Fermentation day with four levels of sodium chloride concentrations 2. Mean ± standard deviation (SD).…”
mentioning
confidence: 99%